A região do Médio Tietê e os primeiros acordes paulistas: o Cururu - Pazetti, Henrique Albiero [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Cururu is an ancient cultural tradition of the São Paulo region of the Middle Tietê and consists of a challenge between singers improvised verses of the sound of the viola caipira. As we understand music as a geographical attribute, we affirm that the landscape, the place, the region and the geographicity the Middle Tietê are on Cururu, just where the Cururu is a fundamental part of the constitution of this region. In carrying out this task on hold you for Humanistic Geography which allowed us to grasp the Cururu the existential route, intimate and organic way, seeking the essence of this culture by living places and talks with people who so strongly appreciate this rustic tradition

O Cururu é uma antiga tradição cultural da região paulista do Médio Tietê e consiste em um desafio de versos improvisados entre cantadores ao som da viola caipira. Como entendemos a música como um atributo geográfico, afirmamos que a paisagem, o lugar, a região e a geograficidade do Médio Tietê estão presentes no Cururu, da mesma maneira em que o Cururu é parte fundamental da constituição desta região. Para a realização desta tarefa nos amparamos pela Geografia Humanista que nos permitiu apreender o Cururu pela via existencial, de maneira íntima e orgânica, buscando a essência desta cultura por meio da vivência dos lugares e das prosas com as pessoas que tão fortemente apreciam esta tradição caipira
Keywords: Human geography; Geografia humana; Cultura popular; Cururu (Canto popular); Viola; Caipiras; Tietê, Rio, Bacia (SP)